Enhanced bio-recovery of aluminum from low-grade bauxite using adapted fungal strains - Shah, Syed Sikandar [UNESP]; Palmieri, Mauricio Cesar; Sponchiado, Sandra Regina Pombeiro [UNESP]; Bevilaqua, Denise [UNESP] (Springer Nature, 2020)
Filamentous fungi have been proved to have a pronounced capability to recover metals from mineral ores. However, the metal recovery yield is reduced due to toxic effects triggered by various heavy metals present in the ore. The current study highlights the fungal adaptations to the toxic effects of metals at higher pulp densities for the enhanced bio-recovery of aluminum from low-grade bauxite. In the previous studies, a drastic decrease in the aluminum dissolution was observed when the bauxite pulp density was increased from 1 to 10% (w/v) due to the high metal toxicity and low tolerance of Aspergillus niger and Penicillium simplicissium to heavy metals. These fungi were adapted in order to increase heavy metal tolerance of these fungal strains and also to get maximum Al dissolution. A novel approach was employed for the adaptation of fungal strains using a liquid growth medium containing 5% bauxite pulp density supplemented with molasses as an energy source. The mycelia of adapted strains were harvested and subsequently cultured in a low-cost oat-agar medium. Batch experiments were performed to compare the aluminum leaching efficiencies in the direct one-step and the direct two-step bioleaching processes. FE-SEM analysis revealed the direct destructive and corrosive action by the bauxite-tolerant strains due to the extension and penetration of the vegetative mycelium filaments into the bauxite matrix. XRD analysis of the bioleached bauxite samples showed a considerable decline in oxide minerals such as corundum and gibbsite. Results showed a high amount of total Al (≥ 98%) was successfully bioleached and solubilized from low-grade bauxite by the adapted fungal strains grown in the presence of 5% pulp density and molasses as a low-cost substrate. [Figure not available: see fulltext.].
Keywords: Aluminum; Bio-recovery; Cane molasses; Filamentous fungi; Tolerance